The Effect of Binder on Hydroxyapatite(HAP) Properties and Surface Roughness when machining - WAN, EZZRA; RAFAI, NOOR HAKIM (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The increasing number of road accidents often leads to bone damage, which may require surgery. To help with bone replacement, hydroxyapatite (HAP), a bio ceramic that closely resembles the mineral found in human bone, has been used. To make the HAP hold together, water-soluble binders like PEG and PVA are added. Four different samples of hydroxyapatite, zinc and magnesium were made with different amounts of binder to study how the binders affect the mechanical properties and surface roughness of the bio ceramic. The samples were prepared by dry mixing the materials and compacting them. The amount of PEG and PVA used ranged from 1% to 4% by weight. All sample were containing 2.5% zinc and 2% magnesium.